Islamic Education Model Based on the Qur'an and Hadith: Relevance for the Digital Age - Irmawati; St. Nurhayati Ali; Syamsuriani (Universitas Muhammadiyah Palu, 2025)
Islamic education based on the Qur'an and Hadith is the main foundation in educating Muslims. However, with the advancement of digital technology, it is important to explore how this educational model can adapt to the changing times, but on the other hand it also poses challenges and negative influences on human development. This research aims to analyze the relevance of Islamic education models based on the Qur'an and Hadith in the digital era. With a qualitative approach and a literature study, this study identifies ways in which technology can be applied to teach Islamic values without sacrificing the essence of religious teachings. The results of the study show that digital technology, when used wisely, can expand access to Islamic education and convey religious values in a more effective and efficient way, as well as relevant to the needs of the digital generation. In addition, the challenges and opportunities that arise in combining technology with religious teachings were also discussed, as well as the role of teaching the Qur'an and Hadith in the formation of character in accordance with Islamic guidance. It is hoped that this Islamic education model is not only relevant to the needs of the times, but also maintains the integrity of Islam in the face of global changes.